(untitled) (Journal of Mathematical Study, 2025)
Fukaya and Yamaguchi conjectured that if M^n is a manifold with nonnegative sectional curvature, then the fundamental group is uniformly virtually abelian. In this short note we observe that the conjecture holds in dimensions up to four.